2006
DOI: 10.1080/03008200600584124
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-4 and Cartilage Oligomeric Matrix Protein form Heterooligomers in Equine Tendon

Abstract: Injuries of the equine superficial digital flexor tendon are common in racing horses. Knowledge of the tendon matrix composition is crucial to understand physiological and pathological processes in the tendon. The aim of this study was to analyze TSP-4 expressed in equine tendon. Equine tendons were extracted with 10 mM EDTA-containing buffer and TSP-4 purified with ion-exchange chromatography followed by heparin affinity chromatography. The purified TSP-4 was analyzed by one- and two-dimensional SDS-PAGE, imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Studies of bovine, equine and human TSP4 have shown that it localizes to tendons (Hauser et al, 1995; Chen et al, 2000; Södersten et al, 2006). To determine if the functional roles of zebrafish Tsp4b are evolutionarily conserved, we injected recombinant human TSP4 (2 ng/embryo) into the interstitial space between myofibers of 60 hpf Tsp4b-deficient embryos.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of bovine, equine and human TSP4 have shown that it localizes to tendons (Hauser et al, 1995; Chen et al, 2000; Södersten et al, 2006). To determine if the functional roles of zebrafish Tsp4b are evolutionarily conserved, we injected recombinant human TSP4 (2 ng/embryo) into the interstitial space between myofibers of 60 hpf Tsp4b-deficient embryos.…”
Section: Resultsmentioning
confidence: 99%
“…Because Tsps interact with other Itg ligands (e.g., Lam, Col, Fn) in vitro it has been debated as to whether Tsps play instructive or merely permissive roles in ECM organization and cell-ECM interactions (Narouz-Ott et al, 2000; Södersten et al, 2006; Tan and Lawler, 2009). In Drosophila , by virtue of its canonical RGD motif, Tsp plays a primary role as an Itg ligand in developing tendons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mCa 2ϩ mutant may also serve as a dominant negative mutant for Thbs5/COMP, since Thbs4 and Thbs5/COMP can assemble as heteropentamers in vivo (54). Regardless, the lack of secretion by the mCa 2ϩ mutant suggests that Ca 2ϩ binding or the sensing of ER Ca 2ϩ is required for proper folding and/or trafficking of Thbs4.…”
Section: Discussionmentioning
confidence: 99%
“…Oligomerization of TSP-1 into trimers occurs through noncovalent association of the coiledcoil domains (Vischer et al 1985;Prabakaran et al 1996). Although TSPs are predominantly homooligomers, natural heteropentamers of TSP-4 and TSP-5/COMP subunits occur in tendon (Hecht et al 1998;Södersten et al 2006).…”
Section: Cell Biology Of Thrombospondins Expression and Synthesis Of mentioning
confidence: 99%